New Multiplexing Technique Based On Return-To-Zero Duty-Cycles - Abdalla Elhag, Mohamed Faisal (2007)

(untitled)
The ever increasing demand for higher speed data transmission is now accelerated more than ever, derived by the requirements of new applications that require very high bandwidths. The huge amount bandwidth available on transmission links such as optical fibers is shared by multiple users using multiplexing techniques. Although commercially available multiplexing techniques help utilizing transmission bandwidth, they are yet to exploit the full bandwidth available due to the speed bottleneck imposed by electronics. To better utilize the transmission bandwidth and release the electronic bottleneck this study proposes a multiplexing technique based on different Return-to-Zero (RZ) duty-cycles. Different users are assigned different RZ duty-cycles. These RZ signals modulate a Continuous Wave CW laser carrier before being multiplexed together using passive couplers. The resulting multiplexed signal forms a multilevel step-down signal. This feature enables channel demultiplexing to be performed electronically at single user baud rate, which is very economic. In this thesis the system design is developed and implemented in the optical domain.Theoretical study of the system limitations is also presented. Due to cost, time, and flexibility constraints, OptiSystems and MATLAB simulators are used in the design and implementation of the proposed technique and to evaluate the performance of the system under different configurations. The system’s performance is investigated back-to-back and after transmission over Standard Single Mode Fiber (SSMF). The system tolerance to signal impairments is investigated. The impairments considered in this study are the dispersion, fiber nonlinearities and amplifier noise. The system tolerance to chromatic dispersion is found to be very poor compared to Time Division Multiplexing (TDM) systems. To reduce the effect of dispersion the study proposes a synchronization technique that gave four times improved dispersion tolerance. The use of dispersion compensating techniques is also recommended as they completely eliminate the dispersion effect. The system is affected by two main nonlinear effects; Self Phase Modulation (SPM) and Stimulated Brillouin Scattering (SBS). Simulation results investigation showed that dispersion pre-compensation reduces the SPM effect and raises the maximum power limit set by this nonlinear phenomenon. This thesis makes two primary contributions. First, this thesis introduces the theory and working principle of the duty-cycle division multiplexing technique which is both economic and less complex than conventional multiplexing techniques. Second, the thesis evaluates the performance of the proposed technique for different design configurations and signal impairments